Insurgency in Nigeria: The Prognosis and its Effects on the Nigerian Politics: Array - Igbini, Mevayerore Daniel (Journal of Danubian Studies and Research, 2020)
Since Nigeria returned to civil rule in May 1999 after several years of military rule, the nation hasn’t enjoyed peaceful moment due to the activities of insurgent groups’ and criminal gangs such as Boko Haram, ISWAP, bandits, armed robbers, Kidnappers and Fulani herdsmen. In light of these ugly and perturbing scenarios this study examined the causative factors of insurgency, as well as crimes in Nigeria. The study, thus, relates this to corruption, nepotism, ethnic consciousness, mediocracy, marginalisation, extreme social deprivation and religious extremism. The study considers the effects of these on the nation’s politics, as the prognoses if these challenges had persisted longer than expected. To achieve this, the study adopted historical research design which is qualitative and explorative in nature, implying that data used in the study were derived from Secondary sources, via books, journal publications, government official documents, internet sources, among others. The study adopted Frustration-Aggression and Relative Deprivation theories to examine the causative factors or reasons why people resort to insurgency, crimes and other forms of unrests as alternative means to register their grievances against the government. Useful recommendations in the form of articulated policy frameworks were presented to stem this ugly trend.